Pengaruh Kepuasan Kerja terhadap Kinerja Pegawai di RSUD Petanang dengan Komitmen Organisasi sebagai Variabel Intervening - Delima Delima; Suyadi Suyadi; Rudi Azhar (INDO PUBLISHING, 2026)
This study aims to determine the effect of job satisfaction on employee performance at Petanang Regional Hospital with organizational commitment as an intervening variable. This study used a quantitative approach with a survey method by distributing questionnaires to 43 Petanang Regional Hospital employees. Data were analyzed using the Partial Least Squares (PLS) method with the help of SmartPLS. The results showed that job satisfaction significantly influenced employee performance through organizational commitment as an intervening variable. This indicates that job satisfaction will be more effective in improving employee performance if accompanied by strong organizational commitment.